Organisational resources and product innovation performance: an empirical study on Malaysian electronic and electrical industry / Malvern Abdullah - Abdullah, Malvern (2010)
In a hypercompetitive business environment, new product innovation has become one of the most important criteria for firm's success. The most common question that has attracted much attention among scholars and practitioners is as to why some firms perform better while the others do not. In spite of numerous studies on this subject, there is still a need to investigate the factors that contribute to product innovation performance of the Malaysian manufacturing firm. To probe further, this research is conducted by focusing on the key factors that might better explain product innovation performance of the firm. This research explores the relationship between the organizational resources and the firm's product innovation performance. The Resource-Based View of the firm is adopted as theoretical guidance in this empirical research.